Appraisal in the Jakarta Post Article Entitled “Ending Poverty, Ending Violence Against Women” - Ni Putu Era Marsakawati (Master Program in Linguistics, Diponegoro University, 2016)
In communication, humans may express their ideas by involving their attitudes, feelings, judgement, or emotions that can be identified from the expressions or words used. There is a system called appraisal can be used to study interpersonal meanings of the utterances. This study aims at investigating types of appraisals in the Jakarta Post article entitled Ending Poverty, Ending Violence against Women and finding out which appraisal mostly occurred in the article. The procedures of data collection were a) identifying the appraisal items; b) classifying the appraisal items; c) calculating the occurrence of each category; d) summarizing the kinds of appraisal items; e) interpreting the appraisal items. The obtained data were analyzed quantitatively. The result shows that appreciation, affect, judgment, and amplification are used in the article; and the most dominant category used is judgment. This implies that in writing articles in newspapers, the writers tend to give judgement on the issues discussed.